In-situ study of the carbon gasification reaction of highly oriented pyrolytic graphite promoted by cobalt oxides and the novel nanostructures appeared after reaction. (March 2020) - Morales, C.; Díaz-Fernández, D.; Prieto, P.; Lu, Y.H.; Kersell, H.; Campo, A.del; Escudero, C.; Pérez-Dieste, V.; Ashby, P.; Méndez, J.; Soriano, L.
Abstract: Cobalt interaction and its effects on carbon-based systems at the nanoscale have recently attracted much attention in different fields, such as catalysis of carbon nanotubes or graphene and graphite nano-patterning taking advantage of its ferromagnetic behavior. Experiments performed in our laboratories show how the re-oxidation process of two equivalent monolayers of CoO deposited on highly oriented pyrolytic graphite at 400 °C leads to the formation of nanochannels at lower temperature than using other methods. Here we present the in-situ characterization of the carbon gasification reaction that drives this process by means of near ambient pressure X-ray photoelectron spectroscopy performed at the ALBA synchrotron facility. The reason why this reaction takes place at such low temperature compared to other methods is due to the weakening of the carbon σ bonds by the initial CoO wetting layer formed at the early stages of growth on the graphite surface. Besides nanochannels, ex-situ atomic force microscopy measurements also show the appearance of two more kinds of nanostructures: nano-strips and nano-rings. The appearance of these nanostructures reveals the impressive modification of the surface after the re-oxidation process mediated by the cobalt oxide. Graphical abstract: Image 1